2013
DOI: 10.1128/aac.01098-13
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interaction between Maraviroc and Fosamprenavir-Ritonavir: an Open-Label, Fixed-Sequence Study in Healthy Subjects

Abstract: dThis open-label, fixed-sequence, phase 1 study evaluated the pharmacokinetic interaction between maraviroc (MVC) and ritonavir-boosted fosamprenavir (FPV/r) in healthy subjects. In period 1, subjects received 300 mg of MVC twice daily (BID; cohort 1) or once daily (QD; cohort 2) for 5 days. In period 2, cohort 1 subjects received 700/100 mg of FPV/r BID alone on days 1 to 10 and then FPV/r at 700/100 mg BID plus MVC at 300 mg BID on days 11 to 20; cohort 2 subjects received FPV/r at 1,400/100 mg QD alone on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“… 92 Fosamprenavir (FPV), an APV pro-drug, is used as a slow-release version of APV. In a treatment regimen including FPV, RTV, and MVC, MVC AUC and Cmax increased by 249% and 152%, respectively; 94 APV AUC and Cmax decreased by 35% and 34%, respectively; 94 RTV AUC and Cmax decreased by 34% and 39%, respectively. 94 While FPV/RTV increasing MVC concentrations is not surprising, since both are CYP3A4 inhibitors, the mechanisms of MVC reducing RTV and FPV concentrations are not known.…”
Section: Mvc Drug–drug Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“… 92 Fosamprenavir (FPV), an APV pro-drug, is used as a slow-release version of APV. In a treatment regimen including FPV, RTV, and MVC, MVC AUC and Cmax increased by 249% and 152%, respectively; 94 APV AUC and Cmax decreased by 35% and 34%, respectively; 94 RTV AUC and Cmax decreased by 34% and 39%, respectively. 94 While FPV/RTV increasing MVC concentrations is not surprising, since both are CYP3A4 inhibitors, the mechanisms of MVC reducing RTV and FPV concentrations are not known.…”
Section: Mvc Drug–drug Interactionsmentioning
confidence: 99%
“…In a treatment regimen including FPV, RTV, and MVC, MVC AUC and Cmax increased by 249% and 152%, respectively; 94 APV AUC and Cmax decreased by 35% and 34%, respectively; 94 RTV AUC and Cmax decreased by 34% and 39%, respectively. 94 While FPV/RTV increasing MVC concentrations is not surprising, since both are CYP3A4 inhibitors, the mechanisms of MVC reducing RTV and FPV concentrations are not known. This may involve protein-binding displacement, which is associated with increase in unbound FPV and RTV ready to be metabolized.…”
Section: Mvc Drug–drug Interactionsmentioning
confidence: 99%
“…Maraviroc was approved based on the MOTIVATE trials comprised of 85% individuals with European ancestry (Gulick et al, 2008) and most previous maraviroc pharmacokinetic studies were conducted in participants with European ancestry, with the median percentage of participants with European ancestry at 78.5% (Abel et al, 2008a,b,c,d,f;Chan et al, 2008;Pozniak et al, 2008;Dumond et al, 2009;Andrews et al, 2010;Ramanathan et al, 2010;Brown et al, 2011;Kakuda et al, 2011;Gruber et al, 2013;Mora-Peris et al, 2013;Taiwo et al, 2013;Vourvahis et al, 2013). A few studies compared maraviroc concentrations in individuals with African ancestry with individuals with European ancestry and concluded that there were no differences or higher concentrations in individuals with African ancestry (FDA, 2007;Okoli et al, 2012), which may be due to the use of CYP3A inhibitors such as ritonavir in the optimized background therapy in which CYP3A5 activity may have been inhibited in individuals who are carrying CYP3A5*1 allele.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence versus absence of ketoconazole 400 mg once daily for 9 days, maraviroc AUC ratio (90% confidence interval [CI]) was 5.0‐fold (4.0‐6.3) . Except for saquinavir/ritonavir, in the presence versus absence of protease inhibitors maraviroc AUC was increased <5‐fold (Figure ) . The effects of ketoconazole and ritonavir on CYP3A substrates triazolam, alfentanil, and avanafil were similar, with substrate AUC increased >9‐fold (Table ) …”
Section: Resultsmentioning
confidence: 98%
“…33 Except for saquinavir/ritonavir, in the presence versus absence of protease inhibitors maraviroc AUC was increased <5-fold (Figure 3). [33][34][35][36] The effects of ketoconazole and ritonavir on CYP3A substrates triazolam, alfentanil, and avanafil were similar, with substrate AUC increased >9-fold (Table 2). [37][38][39][40][41]…”
Section: Effect Of Protease Inhibitors On the Pk Of Cyp3a Substratesmentioning
confidence: 97%